BUDIDAYA PADI SAWAH ORGANIK UNTUK PEMULIHAN KESEHATAN TANAH DAN PENGURANGAN RESIDU PESTISIDA PADA PRODUK HASIL PERTANIAN - Valentino Valentino; Imam Wahyudi; Irwan Lakani; Sri Anjar Lasmini; Usman Made; Idham Idham (Jurnal PkM Pengabdian kepada Masyarakat, 2022)
The tendency of more intensive use of chemicals in agricultural cultivation activities causes an imbalance of other nutrients and decreases the content of soil organic matter. This causes degradation of soil fertility and residues of active pesticides that threaten the sustainability of farming. The community partnership program (PKM)aimed to provide solutions to problems faced by partners in both the production and management fields by providing counseling, demonstrations and assistance. The method activities is participatory rural appraisal (PRA) in applying appropriate technology and empowerment, with partners in these activities being members of the "Batu Sari" farmer group in Astina Village, Torue District, Parigi Moutong Regency. The results of the implementation of community partnerships show an increase in knowledge and skills and attitudes of farmers. The production of organic fertilizers, vegetable pesticides and bioinsecticides carried out by the activity participants went well and could be used as expected. The system of rice intensification (SRI) cropping system can be implemented by partner farmers. partner farmer groups become independent in carrying out their farming activities using assembled technology that has been practiced